A critical analysis of The Royal College of Physicians and Surgeons of Canada examination experience - MacFarlane, Malcolm M (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
The Royal College of Physicians and Surgeons of Canada (RCPSC) plays a leading role in specialty and subspecialty post graduate medical education (PGME) in Canada. As the RCPSC accredits PGME programs, these programs are structured to meet the RCPSC Competence by Design model and their CanMEDS roles. RCPSC Certification is required by Medical Regulatory Agencies (MRAs) across Canada as a condition of entry to independent practice. The RCPSC relies heavily on the use of high-stakes subject examinations as a key component of its Certification process. Recently, questions have been raised regarding the usefulness of such high-stakes examinations. If such examinations are to be fair and equitable, they must be designed and implemented in accordance with best practices for educational testing and the processes for implementation and grading must be transparent and fair. This paper reviews the recent literature on high-stakes examinations and best practices in examination construction, references the findings of a survey of RCPSC examination experiences conducted by the Society for Canadians Studying Medicine Abroad exploring the perception of respondents, and raises concerns regarding RCPSC examinations related to validity, reliability, and fairness. The paper concludes by recommending closer scrutiny of RCPSC examination processes by interested stakeholders and by provincial MRA's who delegate entry to practice decisions to the RCPSC.